(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
This paper presents an analysis of the key factors that, seen from the point of view of entrepreneurs in the software development industry in Colombia, may have a positive effect on the competitiveness of this sector. The starting point of this research is based on improvement opportunities for these companies, taking into account the attractive aspect of this industry due to its high degree of innovation and value-added products. The research was developed with a mixed approach, with an exploratory and a descriptive scope; performing an interpretative work on bibliographic sources and subsequently designing an instrument for acquiring data related to factors that influence the competitiveness of the sector. From these results, a correlation analysis of variables, useful for purposes of sectoral intervention was performed. As a result, there is a correlation between competitiveness and the variables associated with government support, quality of education, existing certifications and processes of economic openness. These results are expected to be useful in promoting programs, plans, and sectoral projects for continuous improvement of the companies that are part of the analyzed sector.